2008
DOI: 10.1097/ccm.0b013e318180c1eb
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with suspected propofol infusion syndrome

Abstract: A number of characteristics are independently associated with higher mortality in patients with suspected propofol infusion syndrome, only some of which are currently reflected in the package insert. Further research should focus on prospectively evaluating the mortality scoring system in patients with suspected propofol infusion syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 43 publications
1
69
0
6
Order By: Relevance
“…Si bien un estudio prospectivo más reciente encontró una incidencia mucho menor (1,1%), los pacientes incluidos recibieron dosis más bajas de propofol (5) . Los reportes de mortalidad atribuible al SIP oscilan entre 30% y 80% (5,6) . La dosis acumulada de propofol, la presencia de síntomas cardíacos, hipotensión arterial, fiebre, acidosis metabólica, falla renal, la edad avanzada y el TEC son factores de riesgo que aumentan la mortalidad del SIP (2,6) .…”
Section: Discussionunclassified
“…Si bien un estudio prospectivo más reciente encontró una incidencia mucho menor (1,1%), los pacientes incluidos recibieron dosis más bajas de propofol (5) . Los reportes de mortalidad atribuible al SIP oscilan entre 30% y 80% (5,6) . La dosis acumulada de propofol, la presencia de síntomas cardíacos, hipotensión arterial, fiebre, acidosis metabólica, falla renal, la edad avanzada y el TEC son factores de riesgo que aumentan la mortalidad del SIP (2,6) .…”
Section: Discussionunclassified
“…23 The mortality is high, reported to be 30% overall, but as high as 83% dependent upon the clinical manifestations. 24 The mortality is higher in males compared with females, younger patients and those with more severe clinical features. 24 PRIS is thought to be caused by the effect of propofol inhibiting the mitochondrial respiratory chain or impairing mitochondrial fatty acid metabolism.…”
Section: Propofol Infusion Syndromementioning
confidence: 99%
“…24 The mortality is higher in males compared with females, younger patients and those with more severe clinical features. 24 PRIS is thought to be caused by the effect of propofol inhibiting the mitochondrial respiratory chain or impairing mitochondrial fatty acid metabolism. It occurs more often with high doses and longterm use of propofol (>4 mg/kg/h for more than 48 h) and in patients receiving catecholamines and glucocorticoids.…”
Section: Propofol Infusion Syndromementioning
confidence: 99%
“…This study reported a mortality of rate of 18%, but an analysis of the Food and Drug Administration's MedWatch system noted 30% mortality in cases of PRIS. 4 Various mechanisms have been proposed for the pathophysiology of PRIS. 2,5 To summarize, propofol impairs function of the mitochondrial respiratory chain.…”
Section: Introductionmentioning
confidence: 99%